KOMPOSISI ATAU PEMAJEMUKAN DALAM BAHASA INDONESIA - Ikawati, Erna (FORUM PAEDAGOGIK, 2016)
Compounding is the process of morphological form of the coupling of two or more basic forms that results in one word. Characteristics of the compound word is a compound word formed a sense, consist of basic words, high usage frequency. Compound words are formed according to the law endocentric DM (explained-explained). This compound distinguishes endocentric and ecosentrist.